ANALYSIS OF SLOPE STABILITY DUE TO ILLEGAL GOLD MINING IN BENGKAYANG REGENCY - Saputra, Andrianus; Priadi, Eka; Rustamaji, Rustamaji (Jurnal Teknik Sipil, 2024)
Illegal gold mining is extracting gold without a formal license from the government or competent authority. It presents a significant environmental and geological challenge in Bengkayang Regency, Indonesia. This practice, carried out without proper authorization or adherence to safety regulations, is recognized as a significant cause of slope instability in the area.This study analyzes slope stability from unlicensed gold mining in Kinande Village, Bengkayang Regency. It uses manual Fellenius calculations and Geo Studio/Geo Slope 2023 software to determine the Safety Factor (SF) for potential landslides, assuming circular landslide planes are unaffected by earthquakes.Laboratory tests revealed varying soil types and properties at these points, impacting shear strength and slope stability. Loamy soils exhibit high cohesion but low internal friction, making them susceptible to instability. Sandy soils lack cohesion and rely on particle friction. Shear strength parameters like cohesion (c) and internal friction angle (Ï†) are critical in assessing slope stability. The study employed the Fellenius method and Geo Studio 2023 software to analyze slope stability, with safety factor (SF) results indicating potential hazards. Mining in plain areas showed favorable SF values (1.5), suggesting activity safety. Conversely, mining in mountainous and watercourse areas exhibited lower SF values (1.5), indicating instability and safety risks. Recommendations include stratified mining practices to maintain stable slopes and ensure miner safety. This research contributes to understanding geohazards and proposes measures for enhanced safety, environmental sustainability, and regulatory governance in mining areas. Understanding and analyzing these factors are crucial for the stability and safety of geotechnical projects, ensuring balanced shear stress and shear strength for slope stability.